MOORA METHOD FOR LECTURER RECOMMENDATIONS THESIS GUIDE - Petti Indrayati Sijabat; Nuraisana Nuraisana; Endra AP Marpaung (Sean Institute, 2022)
Achieving satisfaction in handling final student graduation is the most important situation to achieve service quality satisfaction in doing a service. Thesis is a student's scientific writing as one of the requirements for graduating from college, supporting the completion of the work involving a supervisor with the tasks of ensuring that it fits the topic with the main lesson in the thesis. Problems in the preparation of the thesis with several phenomena that occur, namely students cannot complete it on time according to important dates determined by the Study Program, Lecturers do not have sufficient competence on the topics raised by students, Determination of Supervisors is still focused on the quota that has been set. ensure without ascertaining whether the lecturer concerned is able to provide guidance on the topics provided. This study provides recommendations for study programs in determining text-based supervisors using the MOORA method, with the application that will be developed it can make it easier for study programs to determine thesis supervisors so that students can complete thesis on time because it involves supervisors who have competence in their fields.